2023
DOI: 10.3389/fpls.2023.1162695
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing features of Lycium L. species (family Solanaceae) distributed in Egypt based on their anatomical, metabolic, molecular, and ecological characteristics

Abstract: Among the 70–80 species of the genus Lycium (family Solanaceae) disjunctly distributed around the world, only three are frequently distributed in different locations in Egypt. Due to the morphological similarities between these three species, there is a need for alternative tools to distinguish them. Thus, the objective of this study was to revise the taxonomic features of Lycium europaeum L., Lycium shawii Roem. & Schult., and Lycium schweinfurthii var. aschersonii (Dammer) Feinbrun in consideration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 86 publications
0
1
0
Order By: Relevance
“…Moreover, L. schweinfurthii extracts showed sedative, analgesic, antidepressant, and anticonvulsant activity in mice (Bazine et al, 2023;Sherif et al, 2022). In a recent study, 1-heptatriacotanol, which is also known to have anti-hypercholesterolemic effects (Junwei et al, 2018), and lupeol, which has a wide range of proven biological activities to prevent cancer, coronary, and hepatic diseases (Wal et al, 2015), were also found in L. schweinfurthii plants (Ragab et al, 2023). Lupeol is a pentacyclic triterpenoid known from lupin seeds, g trees, and rubber plants.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, L. schweinfurthii extracts showed sedative, analgesic, antidepressant, and anticonvulsant activity in mice (Bazine et al, 2023;Sherif et al, 2022). In a recent study, 1-heptatriacotanol, which is also known to have anti-hypercholesterolemic effects (Junwei et al, 2018), and lupeol, which has a wide range of proven biological activities to prevent cancer, coronary, and hepatic diseases (Wal et al, 2015), were also found in L. schweinfurthii plants (Ragab et al, 2023). Lupeol is a pentacyclic triterpenoid known from lupin seeds, g trees, and rubber plants.…”
Section: Introductionmentioning
confidence: 99%